Antibiotics in Orthopedic Infections (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The management of orthopedic infections has continuously been gaining increasing interest in the past few years. Various developments of new techniques have enhanced pre- and intraoperative diagnostics, leading to an increased number of identified pathogen organisms in septic but also assumed aseptic revisions. In addition to surgical debridement, knowledge about the systemic and local antibiotic therapy of bone and joint infections is an indispensable premise for a successful outcome. This Special Issue deals with all these topics and more, and it includes research articles as well as a review.